Groundwater in Rio de Janeiro State and on the Metropolitan Coastal Plains: Current Overview and Perspectives for the Use of Natural Resources - Simone Lisboa Santos Silva (Espaço Aberto, 2011)
This article treats the main threats to water resources in Quaternary terrain with level and gently inclined morphology located on the coastal plains of the Metropolitan Region of Rio de Janeiro. Due to favorable terrain conditions, the coastal plains are subject to multiple uses, of which sand extraction is analyzed here with regard to its influence on water quality and the most vulnerable aquifers are identified. The situation is made worse due to the absence of recovery projects after extraction ceases. The importance of water resources vis-à-vis other natural resources is seen in recuperation strategies based on the lakes formed by flooding of the excavated areas. Lastly, the strategic importance of groundwater reserves is highlighted as an alternative for an unfavorable scenario of deficit in normal water supply.